Introduction To Basic Mathematical Concepts Through Learning Media - Ghina Fatihatul Jannah; Naelatu Robicha; Khansah Inas Syarifah; Rasilah Rasilah (MASI Mandiri Edukasi, 2025)
Understanding fundamental mathematical concepts is essential for developing students' logical reasoning, critical thinking, and problem-solving abilities. This study employs a literature review methodology to analyze foundational mathematical concepts—such as numbers, arithmetic operations, geometry, algebra, and statistics—and their impact on students' learning and cognitive development. The findings indicate that interactive tools, cultural contexts, and hands-on learning media significantly enhance students' comprehension and retention of these basic concepts. Studies reviewed include applications of traditional games, visual aids, and realistic mathematics approaches, which help bridge abstract concepts with everyday life, thus fostering a deeper, more applicable understanding of mathematics. This research provides insights for educators to utilize varied, engaging approaches that support students' foundational knowledge, encouraging better academic outcomes and practical skills. The findings suggest that contextual and interactive methods in early mathematics education are crucial for cultivating a robust foundation for further learning.